2009
DOI: 10.1021/ja8098867
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexes of Cinchonine as Chiral Building Blocks: A Strategy for the Construction of Nanotubular Architectures and Helical Coordination Polymers

Abstract: The first chiral bipyridyl-type metalloligands based on aluminum derivatives of cinchonine (CN-H) were synthesized and characterized by single-crystal X-ray diffraction studies. These bischelate complexes, (CN)(2)AlX [X = Cl (1a), Me (1b)] were found to be effective building blocks for the preparation of novel helical nanotubular architectures as well as chiral bimetallic coordination polymers, as demonstrated by the rational synthesis of a helical structure formed by 1a and ZnCl(2). The applied methodology st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…[ 105 ] Treatment of aluminum complexes (AlMe 2 Cl or AlMe 3 ) with 2 equiv of cinchonine ( L 17 Figure 25 ). [ 100 ] The 33 cm high chiral column was prepared by loading a glass tube (8 mm inner diameter) with a suspension of 56 in 10% solution of DMF in CH 2 Cl 2 , and a mixture of the sulfi de (PhSMe) and H 2 O 2 was charged directly onto the top of the column.. Each probe contained ca.…”
Section: Crystallization Separationmentioning
confidence: 99%
“…[ 105 ] Treatment of aluminum complexes (AlMe 2 Cl or AlMe 3 ) with 2 equiv of cinchonine ( L 17 Figure 25 ). [ 100 ] The 33 cm high chiral column was prepared by loading a glass tube (8 mm inner diameter) with a suspension of 56 in 10% solution of DMF in CH 2 Cl 2 , and a mixture of the sulfi de (PhSMe) and H 2 O 2 was charged directly onto the top of the column.. Each probe contained ca.…”
Section: Crystallization Separationmentioning
confidence: 99%
“…All the four natural compounds, their derivatives and metal complexes have become more and more interesting catalysts for asymmetric syntheses [6]. Recently they play an important role in the preparation of new chiral nanomaterials [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This paper described our work on influence of controlled microwave heating on activity of palladium solid supported (Pd/SS) catalysts in the heterogeneous isomerisation of four natural Cinchona alkaloids. We studied also possibility of analysis and isolation of the geometric isomers Z and E in Δ 3,10 -isomers, as they will be used as chiral ligands [7,8], catalysts and modifiers in asymmetric syntheses [9][10][11][12].…”
mentioning
confidence: 99%
“…Initially we synthesized bischelate aluminum complexes, XAl(CN) 2 (where CN = deprotonated cinchonine), as novel chiral N,N-metalloligands I (Scheme 1), and demonstrated their excellent capability as metallotectons for noncovalent-interaction-driven selfassembly into novel microporous chiral architectures prone to enantioselective sorption, as well as their coordinationdriven self-organization for constructing coordination polymers of helical topology. [11] Herein, we extend this strategy to dinuclear aluminum-cinchone complexes as novel molecular building blocks II to produce flexible homochiral NPMs. We show that the resulting NPMs can compete with classical MOFs as highly selective adsorbents exhibiting unique properties, such as temperature-triggered adsorption as well as very high affinities for H 2 , CO 2 , and CH 4 .…”
mentioning
confidence: 99%
“…We note that the synthesis and spectroscopic characterization of 1 was reported previously and the variable-temperature 1 H NMR studies revealed that it exists in solution as a dimeric five-coordinate adduct of formula [Me 2 Al(m-CN)] 2 with a relatively high activation energy (80.8 kJmol À1 K À1 ) for the dissociation of the AlÀN dative bond. [12] As structural details for [R 2 Al(m-CN)] 2 complexes were still lacking, [13] as well as being encouraged by the above-mentioned results for the monomeric XAl(CN) 2 -type complexes, [11] we put a lot of effort into obtaining single crystals of the title compounds suitable for X-ray diffraction studies. We succeeded when THF was used as the crystallization solvent.…”
mentioning
confidence: 99%